Observation of the Gut Microbiota Profile in C57BL/6 Mice Induced by Plasmodium berghei ANKA Infection - Guan, Wei; Yang, Shuguo; Zhao, Yanqing; Cheng, Weijia; Song, Xiaonan; Yao, Yi; Xie, Yiting; Du, Weixing; Li, Jian (Frontiers in Cellular and Infection Microbiology, 2021)
The genus of Plasmodium parasites can cause malaria which is a prevalent infectious disease worldwide, especially in tropical and subtropical regions. C57BL/6 mice infected with P. berghei ANKA (PbA) will suffer from experimental cerebral malaria (ECM). However, the gut microbiota in C57BL/6 mice has rarely been investigated, especially regarding changes in the intestinal environment caused by infectious parasites. P. berghei ANKA-infected (PbA group) and uninfected C57BL/6 (Ctrl group) mice were used in this study. C57BL/6 mice were infected with PbA via intraperitoneal injection of 1 × 106 infected red blood cells. Fecal samples of two groups were collected. The microbiota of feces obtained from both uninfected and infected mice was characterized by targeting the V4 region of the 16S rRNA through the Illumina MiSeq platform. The variations in the total gut microbiota composition were determined based on alpha and beta diversity analyses of 16S rRNA sequencing. The raw sequences from all samples were generated and clustered using ≥ 97% sequence identity into many microbial operational taxonomic units (OTUs). The typical microbiota composition in the gut was dominated by Bacteroidetes, Firmicutes, Proteobacteria, and Verrucomicrobia at the phylum level. Bacteroidetes and Verrucomicrobia were considerably decreased after PbA infection compared with the control group (Ctrl), while Firmicutes and Proteobacteria were increased substantially after PbA infection compared with Ctrl. The alpha diversity index showed that the observed OTU number was increased in the PbA group compared with the Ctrl group. Moreover, the discreteness of the beta diversity revealed that the PbA group samples had a higher number of OTUs than the Ctrl group. LEfSe analysis revealed that several potential bacterial biomarkers were clearly related to the PbA-infected mice at the phylogenetic level. Several bacterial genera, such as Acinetobacter, Lactobacillus, and Lachnospiraceae_NK4A136_group, were overrepresented in the PbA-infected fecal microbiota. Meanwhile, a method similar to gene coexpression network construction was used to generate the OTU co-abundance units. These results indicated that P. berghei ANKA infection could alter the gut microbiota composition of C57BL/6 mice. In addition, potential biomarkers should offer insight into malaria pathogenesis and antimalarial drug and malaria vaccine studies.